On-farm assessment of cassava root yield response to tillage, plant density, weed control and fertilizer application in southwestern Nigeria - Onasanya, O.; Hauser, S.; Necpalova, M.; Salako, F.K.; Kreye, C.; Tariku, M.; Six, Johan; Pypers, P. (Elsevier, 2021)
Cassava is growing in importance in Nigeria as a food and industrial crop. Current yields are low due to poor soil fertility and because farmers do not use improved germplasm, clean planting material, or improved crop management in Nigeria. To provide feasible agronomic recommendations targeting increased root yield, the effects of tillage intensity, fertilizer application, plant density and weed control were tested in 230 farmers’ fields in southwestern Nigeria over two years. In 2016, tillage treatments were zero, single and double passage with a disc plough, followed by ridging (soil shaping) versus leaving the soil flat. Fertilizer application at 75:20:90 kg ha−1 NPK was tested against a control and two plant densities (10,000 versus 12,500 ha−1) were compared. In 2017, plant density at 10,000 ha−1 and double plough were excluded, while pre- and post-emergence herbicide application versus farmer’s choice of weed control (i.e. manual weeding using hand hoe) was introduced. Cassava was harvested at 12 months after planting, and yields were recorded as fresh root mass. In 2016, double plough (15.9 Mg ha−1) had a minor advantage over single plough (14.3 Mg ha−1), while zero plough produced 12.9 Mg ha−1 (P < 0.001). Ridging increased yield significantly (P < 0.01) by 2.3 Mg ha−1 after single and zero plough, but not after double plough. Across tillage treatments, planting at 12,500 plants ha−1 and fertilizer application increased yields by 1.5 and 4.2 Mg ha−1, respectively. In 2017, ridging resulted in a yield increase of 1.7 Mg ha−1 after single plough and 5.6 Mg ha−1 after zero plough. Fertilizer application increased root yield by 2.9 Mg ha-1 across tillage treatments. The use of herbicides negatively affected cassava yields in zero plough fields, compared with manual weeding. After ploughing, yield in herbicide based and manual weed control were not different. Cassava root yield response to tillage intensity strongly varied across fields, with low-yielding fields commonly responding less frequently to tillage. We conclude that unresponsive fields require measures other than increased tillage intensity to increase cassava root yields and that cost-intensive tillage operations must be targeted to responsive fields together with fertilizer application and improved weed control.